2017
DOI: 10.1186/s13395-017-0126-x
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid acid-induced microRNA-31-5p suppresses myogenic proliferation and differentiation by targeting CamkIIδ

Abstract: BackgroundWe previously reported that Wnt5a/CaMKIIδ (calcium/calmodulin-dependent protein kinase II delta) pathway was involved in the embryonic tongue deformity induced by excess retinoic acid (RA). Our latest study found that the expression of miR-31-5p, which was predicted to target the 3′UTR of CamkIIδ, was raised in the RA-treated embryonic tongue. Thus, we hypothesized that the excess RA regulated Wnt5a/CaMKIIδ pathway through miR-31-5p in embryonic tongue.MethodsC2C12 myoblast line was employed as an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…3A) and DTNA 15) for the seed sequence of miR-27b-3p. We also found another miRNA, miR-31-5p could also complementary match with the 3' UTR of CamkIIδ 14) , but the effects of both miR-27b-3p targeted to DTNA and miR-31-5p to CaMKIIδ were mainly displayed in the late stages of C2C12 myogenic diff erentiation 14,15) . So, whether miR-27b-3p targeted CaMKIIδ aff ected the other processes of myogenesis attracted our attention.…”
Section: Mir-27b-3p Directly Targets 3' Camkiiδutr and Inhibits Camkimentioning
confidence: 66%
See 3 more Smart Citations
“…3A) and DTNA 15) for the seed sequence of miR-27b-3p. We also found another miRNA, miR-31-5p could also complementary match with the 3' UTR of CamkIIδ 14) , but the effects of both miR-27b-3p targeted to DTNA and miR-31-5p to CaMKIIδ were mainly displayed in the late stages of C2C12 myogenic diff erentiation 14,15) . So, whether miR-27b-3p targeted CaMKIIδ aff ected the other processes of myogenesis attracted our attention.…”
Section: Mir-27b-3p Directly Targets 3' Camkiiδutr and Inhibits Camkimentioning
confidence: 66%
“…To explore the molecular mechanism for this, we subsequently did miRNA microarray and identified the dysregulated miRNAs in RA-induced abnormal tongue 15) and studies in this paper, we found that CaMKIIδ was a downstream target of miR-27b-3p. Furthermore, our latest studies also indicated that miR-27b-3p and miR-31-5p could target DTNA 15) and CaMKIIδ 14) respectively at late myogenic diff erentiation stages, implying that miR-27b-3p controls different targets and CaMKIIδ could be regulated by numbers of miRNAs at different stages during myogenic diff erentiation process. These were consistent with the characters and complex regulatory network of miRNAs.…”
Section: Knockdown Of Camkiiδ Impaired the Early Diff Erentiation Of mentioning
confidence: 88%
See 2 more Smart Citations
“…A previous study demonstrated the involvement of the Wnt5a/CaMKII pathway in retinoic acid (RA)-induced developmental abnormalities in mouse genioglossus [17]. Retinoic acid (10 µM) inhibits the proliferation and differentiation of C2C12 cells by upregulating the expression of miR-31-5p and miR-27b-3p and downregulating the expression of CamkIIδ and DTNA [18,19]. Exogenous RA (3 µM) promotes the apoptosis and inhibits the proliferation of epithelial cells lining the labial cervical loop by downregulating the expression of the mesenchymal factor Fgf10, thereby negatively regulating the homeostasis of the incisor stem cell niche.…”
Section: Introductionmentioning
confidence: 99%